PERBEDAAN KECEMASAN DALAM MEMILIH JURUSAN DI PERGURUAN TINGGI PADA SISWA KELAS XII DITINJAU DARI PEMBERIAN BIMBINGAN KONSELING - Navi Navi; Maria Dwi Yanika Hesti Nugraha (Universitas Bunda Mulia, 2012)
This research using quantitative data which includes comparative research or research that aimed to know differences between two variable or more for to know are have difference about anxiety in choose major in college on the students twelve grades observed from guidance and counseling. The research sampling method using purposive sample and size of samples amount 45 students twelve grades Jembatan Lima who get guidance and counseling and 45 students twelve grades Duri Raya who didn’t get guidance and counseling. This research used anxiety scale are reviewed by Dacey & Fiore’s (2002) component. Reliability anxiety scale value in choose major in college on amount .930 consisted 22 item. The analysis data using Mann – U Whitney represent that have differences about anxiety in choose major in college on the students twelve grades Jembatan Lima who get guidance and counseling with the students twelve grades Duri Raya who didn’t get guidance and counseling. Keywords: Anxiety in choose major in college, Guidance and Counseling, and Students twelve grades.